Effects of using collagen and aloe vera grafted fibroin scaffolds on osteogenic differentiation of rat bone marrow mesenchymal stem cells in SBF-enriched cell culture medium - Taher Mohamed, Salma A; Emin, Nuray (IOP Publishing, 2023)
Abstract In the study, collagen and aloe vera were grafted onto silk fibroin with two different methods, and 3D-microporous scaffolds (1F5C4A1 and 2F5C4A1) were formed by lyophilization. Three osteogenic cultures were started by seeding rat bone marrow mesenchymal stem cells (MSCs) and pre-induced MSC (osteoblast (OB)) on biopolymeric scaffolds. The osteogenic medium was enriched with 10% (v/v) simulated body fluid (SBF) to promote mineralization and osteogenic differentiation in one of the MSC cultures and the OB culture. X-ray diffraction (XRD), scanning electron microscopy (SEM), scanning electron microscopy- energy dispersive spectrum (SEM-EDS) analyses on cellular samples and histochemical (alizarin red, safranin-O, alcian blue) and immunohistochemical (anti-collagen-1, anti-osteocalcin, anti-osteopontin) staining showed that bone-like mineralization was occurred by both chemically and cellular activity. In addition, pre-osteogenic induction of MSCs in 2D-cultured was found to promote osteogenesis more rapidly when started 3D-cultured. These results indicated that enrichment of the cell culture medium with SBF is sufficient for in vitro mineralization rather than using high concentrations of SBF. The findings showed that OB cells on the 2F5C4A1 scaffold obtained the best osteogenic activity. Still, other culture media with 10% SBF content could be used for bone tissue engineering under osteogenic induction.
Keywords: Tissue Scaffolds; Tissue Engineering; Osteogenesis; Cell Culture Techniques; Animals; Mesenchymal Stem Cells; Cell Differentiation; Bone Marrow Cells; Collagen; Aloe; Fibroins; Cells, Cultured; Rats